Optimizing Water and Nitrogen Management for Green Pepper (Capsicum annuum L.) under Drip Irrigation in Sub-Tropical Monsoon Climate Regions - Dai, Zhiguang; Zhao, Xinyu; Yan, Hui; Qin, Long; Niu, Xiaoli; Zhao, Long; Cai, Yaohui (Agronomy (Basel), 2023)
Green pepper (Capsicum annuum L.) is one of the major vegetables cultivated in sub-tropical monsoon climate regions. However, with the unreasonable use of water and nitrogen (N) fertilizer, efficient water and N fertilizer management systems need to be identified. The goal of this project was to investigate the coupling effects of different amounts of water and N on green pepper yield, water use efficiency (WUE), as well as N use efficiency (NUE) in sub-tropical monsoon climate regions. The optimum combination of water and N inputs was determined for multi-objective optimization through the multiple regression analysis and the combinations of likelihood functions. The pot experiment was conducted during the green pepper growing seasons (May–September) of 2019 and 2020 in a greenhouse at Nanchang, Jiangxi of China that included three water deficit levels, i.e., mild deficit (W1: 95~80%θFC, %θ field capacity simplified as %θFC), moderate deficit (W2: 80~65%θFC), and severe deficit (W3: 65~50%θFC), and four levels of nitrogen application (Napp) rate, i.e., 6.0 (N1), 3.0 (N2), 1.5 (N3), and 0.0 g plant−1 (N4), for a total of twelve treatments (i.e., 3 × 4) with six replications. Results show that water levels have an extremely significant effect (p < 0.01) on green pepper yield and WUE, but no effect on NUE (p > 0.05). N treatments have significant effects on green pepper yield, WUE, and NUE. Meanwhile, the effects of water levels and N treatment interaction on WUE and NUE were extremely significant (p < 0.01), but varied on yield between the two years. The maximum yields (576.26 and 619.00 g plant−1) occurred when the water level and Napp rate were 80~65%θFC and 6.0 g plant−1. While the water level and Napp rate were 80~65%θFC and 3.0 g plant−1, the WUEs and NUEs reached the maximum, which were 20.14 and 17.71 g L−1, 76.54, and 77.73 g−1 in 2019 and 2020. The dualistic and quadric regression equations of irrigation amount and Napp rate indicated that the yield, WUE and NUE cannot reach the maximum at the same time. By establishing a multiobjective optimization model using combinations of likelihood functions, it was concluded that the water level shall be controlled in 80~65%θFC and the Napp rate is 3.78 g plant−1, which can be used as the suitable strategy of water and N management for the maximum comprehensive benefits of yield, WUE, and NUE for green pepper. The obtained optimum combination of water and N inputs can provide a scientific basis for irrigation and fertilization optimization and management in sub-tropical monsoon climate regions.